DAMPAK KUALITAS PRODUK, PELAYANAN PELANGGAN, HARGA, DAN INOVASI PROMOSI TERHADAP LOYALITAS UMKM DI WILAYAH JAKARTA UTARA - Stieven; Liestyaningrum Rahmadhani Wisnu Putri (MANAJEMEN DEWANTARA, 2025)
The goal of the study is to comprehend how these independent factors affect customer loyalty, the dependent variable, both individually and collectively. A significant focus is placed on the potential role of artificial intelligence in enhancing promotional strategies and service personalization, thereby strengthening customer relationships. The findings are intended to provide actionable insights for MSME owners to develop effective marketing strategies, improve competitiveness, and ensure long-term business sustainability in a competitive local market. A quantitative approach is employed, utilizing a survey method for data collection. The population comprises 16,982 MSME owners in North Jakarta, from which a sample of 150 respondents is selected through purposive samplingThe data analysis will be conducted using SPSS version 25, involving validity and reliability tests, classical assumption tests (normality and multicollinearity), and multiple linear regression analysis to test the proposed hypotheses (H1, H2, H3, H4) both partially (t-test) and simultaneously (F-test). The anticipated results are expected to confirm that product quality, customer service, price, and promotion innovation each have a positive and significant effect on customer loyalty among MSMEs in North Jakarta. The study is expected to provide empirical evidence supporting the integration of AI-driven strategies to enhance customer engagement and retention, offering practical recommendations for MSMEs to build a loyal customer base and secure a competitive advantage in the local economic landscape.